2016
DOI: 10.1007/s00284-016-1163-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Endophytic Bacterial Community in Supposedly Axenic Cultures of Pineapple and Orchids with Evidence on Abundant Intracellular Bacteria

Abstract: Asepsis, defined as the absence of microbial contamination, is one of the most important requirements of plant micropropagation. In long-term micropropagated cultures, there may occasionally occur scattered microorganism growth in the culture medium. These microorganisms are common plant components and are known as latent endophytes. Thus, the aim of this research was to investigate the presence of endophytic bacteria in asymptomatic pineapple and orchid microplants, which were cultivated in three laboratories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
1
12
0
8
Order By: Relevance
“…However, the result of bacterial microbiome was different from the study of other plant, such as rice (Edwards et al, 2015), Arabidopsis (Duran et al, 2018), millet (Jin et al, 2017), Cycas panzhihuaensis (Zheng and Gong, 2019), which suggested that the compartment was the main factor shaping the composition of the bacterial microbiome. It may relate to the growth characteristics of orchids, which fully or partially relies on mycorrhizal fungi for requisite nutrients; meanwhile, some bacteria, such as the mycorrhiza helper bacteria (MHB) were found to be commonly occurring in ectomycorrhiza and in arbuscular mycorriza associations, which assist mycorrhiza formation (Frey-Klett and Garbaye, 2005;Faria et al, 2013;Esposito-Polesi et al, 2017;Li et al, 2017). Nonetheless, very little is known about the composition, structure, and functional activity of bacterial microbiome associated with orchid, let alone the information in G. conopsea.…”
Section: Discussionmentioning
confidence: 99%
“…However, the result of bacterial microbiome was different from the study of other plant, such as rice (Edwards et al, 2015), Arabidopsis (Duran et al, 2018), millet (Jin et al, 2017), Cycas panzhihuaensis (Zheng and Gong, 2019), which suggested that the compartment was the main factor shaping the composition of the bacterial microbiome. It may relate to the growth characteristics of orchids, which fully or partially relies on mycorrhizal fungi for requisite nutrients; meanwhile, some bacteria, such as the mycorrhiza helper bacteria (MHB) were found to be commonly occurring in ectomycorrhiza and in arbuscular mycorriza associations, which assist mycorrhiza formation (Frey-Klett and Garbaye, 2005;Faria et al, 2013;Esposito-Polesi et al, 2017;Li et al, 2017). Nonetheless, very little is known about the composition, structure, and functional activity of bacterial microbiome associated with orchid, let alone the information in G. conopsea.…”
Section: Discussionmentioning
confidence: 99%
“…Each data point represents a mean ± standard error (n = 3). Vertical bars on symbols represent ± SE of the mean the yeast became the dominant microorganism at the wound and adapted to the environment of the wound, and the pathogens lost the ability to seize space, the anthracnose pathogens gradually died because there was no growth space [32]. Therefore, competition for nutrition and space became one of the effective ways for the antagonistic yeast M. pulcherrimato inhibiting C. gloeosporioides.…”
Section: The Competition For Spacementioning
confidence: 99%
“…However, several studies have shown that bacterial endophytes are common in plant tissues grown in vitro and that their beneficial effects on plant growth indicate that they may be useful as growth-promoting agents. In previous studies, a succession of bacterial communities that colonized pineapple microplant organs in vitro were characterized ( Abreu-Tarazi et al, 2010 ) Similarly, endophytic bacteria were isolated from strawberry tissues cultivated in vitro ( Kukkurainen et al, 2005 ; Dias et al, 2009 ), and their beneficial effect on the acclimatization of the seedlings under greenhouse conditions was demonstrated ( Dias et al, 2009 ). Recently, the effects of bacterial endophytes in different in vitro culture phases and in different plant organs of Prunus avium were studied; isolates of the endophytes Rhodopseudomonas palustris and Microbacterium testaceum promoted rooting in two difficult-to-propagate genotypes ( Quambusch et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%